Factors Affecting TKBM Performance at Bitung Port, North Sulawesi: Competency and Training - Frisca Mareyta Pongoh; Hadi Setiawan; Santun Irawan; Teriyanti Btr; Fajar Sutopo (Dinasti International Journal of Education Management And Social Science, 2025)
The loading and unloading process at the port determines the smooth running of the economy, and this cannot be separated from the role of the Loading and Unloading Workers (TKBM) at the port. In its development, TKBM in ports has become very important because it determines the smoothness of the loading and unloading process, so it requires loading and unloading workers with expertise and reliability in using tools during loading and unloading and applying K3 principles. Bitung Port is one of the important factors that drive economic growth and development in North Sulawesi. At Bitung Port, it was confirmed that more than 1000 TKBM were carrying out loading and unloading activities. This research aims to determine the effect of competency and training on TKBM performance at Bitung Port, North Sulawesi. The research method uses quantitative research with data collected through questionnaires. The research results show that TKBM competency and training simultaneously influence TKBM performance at Bitung Port.